Language, Commerce, and Urban Identity: A Socio-Onomastic Study of Coffee Shop Naming Practices in Surabaya - Rachmad, Rio Nur (Southeast Asian Language and Literature Studies, 2025)
This study investigates how coffee shop naming practices in Surabaya function as socio-onomastic acts that negotiate urban identity through linguistic choices. Using a qualitative and document-based approach, the study documented 71 coffee shop names across diverse neighborhoods in Surabaya. Data were analyzed to identify patterns in linguistic structure, language origin, and extra-linguistic factors influencing naming. The findings reveal that coffee shop names are not merely identifiers but strategic socio-onomastic practices that actively construct Surabaya’s hybrid urban identity. The linguistic choices demonstrate continuous negotiation between local rootedness and global modernity—Javanese names index cultural intimacy and authenticity, while English or French names signal cosmopolitan aspirations. References to geography and history further strengthen national belonging distinct from colonial and global identities. This study contributes to the broader understanding of how language, commerce, and culture intersect in Indonesia’s urban linguistic landscape, offering both theoretical insight and practical implications for local branding strategies.